Does Pollution Increase School Absences? - Currie, Janet; Hanushek, Eric A; Kahn, E. Megan; Neidell, Matthew; Rivkin, Steven G (The Review of Economics and Statistics, 2009)
We examine the effect of air pollution on school absences using administrative data for elementary and middle school children in 39 of the largest school districts in Texas merged with air quality information maintained by the Environmental Protection Agency. We address potentially confounding factors with a difference-in-difference-in-differences strategy that controls for persistent characteristics of schools, years, and attendance periods. Of the pollutants considered, we find that high carbon monoxide (CO) levels, even when below federal air quality standards, significantly increase absences. Our results suggest that the substantial decline in CO levels over the past two decades has yielded economically significant health benefits.